A COMPARATIVE STUDY OF QOS OVER IPV4/IPV6 USING OPNET MODELER - Faris Khaleel Al-Fayyadh (مجلة علوم ذي قار, 2019)
The increasing number of internet users around the world and their demand for multimedia applications like VoIP and video conference force the network providers to think about Quality of Services. Since these new applications are sensitive to network performance, the demand for larger bandwidth is increased especially when network parameters like Jitter, End to End (E2E) delay and Packet loss play a very important role to guarantee such application in terms of quality. In such environment, Quality of Service (QoS) is considered to be the most important network performance parameter which has a significant effect on multimedia applications like Voice Over Internet Protocol (VoIP) and others. internet protocol IPv6 was designed to improve QoS supported by internet protocol IPv4 and to enhance the reliability of packet based network to handle such services. This paper considered three queuing systems which are First In First Out (FIFO), Priority Queuing (PQ) and Weighted Fair Queuing (WFQ) as a comparative study to investigate their effects on real-time applications in IPv4 and IPv6 networks support. The proposed simulation environment was executed by Optimized Network Engineering Tools (OPNET) Modeler 14.5 where the simulation results are collected and analyzed. The results show that IPv6 with PQ provides better performance for real-time applications, despite that IPv6 with WFQ is more efficient with low priority traffic.